Cultural psychology of musical experience - Klempe, Sven Hroar (Advances in cultural psychology., 2016)
This book forms a basis and a starting point for a closer dialogue between musicologists, anthropologists and psychologists to achieve a better understanding of the cultural psychology of musical experience. This is done by arranging a meeting point or an arena in which different aspects of psychology and musicology touch and encounters each other due to how the two fields might be defined today. In line with this the book consists of a group of scholars that have their feet solidly grounded in psychology, social science or musicology, but at the same time have a certain interest in uniting them. On this basis it is divided into five parts, which investigates musical sensations, musical experiences, musical transformations, musical fundamentals and the notion of a cultural psychology of music. Thus another aim of this book is to prepare the basis for a further growth of a cultural psychology that is able to include the experiences of music as a basis for understanding the ordinary human life. Thus this book should be of interest for those who want to investigate the mysterious intersection between music and psychology.